Impact of Prostitution Localization (PMD) on the Education and Social of Youth Way Lunik, Bandar Lampung City - Azizah Husin; Putri Kiki Sushella (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the impact of the prostitution environment on the education and social environment of adolescents, education, social (moral and religious) and informal education related to the way parents educate local teenagers living in former localization area.. This study uses a qualitative approach with descriptive data analysis techniques. This research is located in the Teluk Tomini Views of Waylunik Village, Bandar Lampung City. The research subjects were 9 people and the data analysis technique used data collection procedures, data presentation, and drawing conclusions. The data validation technique uses time triangulation and subject triangulation. The results of this study indicate that the impact of the former Scenic Prostitution Localization on youth education is the lack of interest and desire for education because teenagers think education is not an important thing in their lives. The prostitution environment in which teenagers live has a bad influence. Although there are religious activities and parents provide religious education to teenagers, this still affects the personality, moral, social and behavioral development of adolescents. More attention is needed from parents and more encouragement for teenagers to have an interest and desire for education for teenagers who live in former scenic localizations.